Implementasi Standar Pelayanan Minimal Bidang Kesehatan Di RSUD Kota Baubau - Saputra, Dedi Rahmat; Suranto, Suranto (Universitas Muhammadiyah Yogyakarta, 2014)
The hospital has a strategic role in the effort to accelerate the improvement of public health degree. The new para-digm of health care requires hospitals provide quality services according to the needs and wishes of the patient withreference to the code of professional conduct and medical. Performance of health care organizations typically use aminimum standard criteria of service in accordance with the Regulation of the Minister of Health No. 741 / Menkes /Per / VII / 2008. These regulations outline covers; a) basic health services, b) health care referrals, c) epidemiologicalinvestigation and prevention of outbreaks and d) health promotion and community development. The purpose of thisstudy was to determine the implementation of the minimum service standards in the field of health referral at RSUDBaubau and to determine the factors that affect the minimum service standard reference in the field of health at RSUDBaubau. The method used in this research is descriptive qualitative. The data collection techniques in this research isinterview and documentation. Meanwhile, the techniques used to analyze the data in this study is a descriptive analysistechniques. This analysis includes data checking, data grouping, data checking, data analysis and conclusion. Theresults of this experiment showed that the implementation of the minimum service standards in the field of healthreferral at RSUD Baubau has been good. A slight lack of implementation of the health sector MSS reference in RSUDBaubau is the amount of human resources required. The factors that affect the implementation of minimum servicestandard reference in the field of health, namely RSUD Baubau; Communication, disposition and bureaucratic struc-ture. As for the factor of resources because there is still a shortage of only 80% to meet the needs of humanresources at RSUD Baubau.